Mhc‐linked survival and lifetime reproductive success in a wild population of great tits. Issue 2 (28th November 2012) - Sepil, Irem; Lachish, Shelly; Sheldon, Ben C.
Abstract Major histocompatibility complex (Mhc) genes are frequently used as a model for adaptive genetic diversity. Although associations between Mhc and disease resistance are frequently documented, little is known about the fitness consequences of Mhc variation in wild populations. Further, most work to date has involved testing associations between Mhc genotypes and fitness components. However, the functional diversity of the Mhc, and hence the mechanism by which selection on Mhc acts, depends on how genotypes map to the functional properties of Mhc molecules. Here, we test three hypotheses that relate Mhc diversity to fitness: (i) the maximal diversity hypothesis, (ii) the optimal diversity hypothesis and (iii) effect of specific Mhc types. We combine mark–recapture methods with analysis of long‐term breeding data to investigate the effects of Mhc class I functional diversity (Mhc supertypes) on individual fitness in a wild great tit (Parus major) population. We found that the presence of three different Mhc supertypes was associated with three different components of individual fitness: survival, annual recruitment and lifetime reproductive success (LRS). Great tits possessing Mhc supertype 3 experienced higher survival rates than those that did not, whereas individuals with Mhc supertype 6 experienced higher LRS and were more likely to recruit offspring each year. Conversely, great tits that possessed Mhc supertype 5 had reduced LRS. We found no evidence for a selective advantage of Mhc diversity, in terms of either maximal or optimal supertype diversity. Our results support the suggestion that specific Mhc types are an important determinant of individual fitness.